Effect of Emotional Intelligence and Commitment on The Performance Employees at PT. Angkasa Pura II Aceh Sultan Iskandar Muda Airport - Ikhbar, Samsul; Zulfadli; Hadi, Abdul (Indonesian Journal Economic Review (IJER), 2022)
This study aims to determine the effect of emotional intelligence and commitment on the performance of PT Angkasa Pura II employees at Sultan Iskandar Muda Airport, Aceh Besar. The research sample was 101 employees of the company which was taken by the census method. The data was collected using a questionnaire and then the data was analyzed using multiple linear regression statistical equipment. The study found that emotional intelligence and commitment have a positive effect on the performance of PT Angkasa Pura II employees at Sultan Iskandar Muda Airport, Aceh Besar. Among the two variables, the commitment variable has a very dominant influence on performance when compared to emotional intelligence. The results of statistical tests show that the calculated F value > F table and the t arithmetic value of each variable is also greater than the t table value, it can be interpreted either simultaneously or partially the two variables (emotional intelligence and commitment) have a significant (significant) effect on employee performance of PT Angkasa Pura II Sultan Iskandar Muda Airport, Aceh Besar. Therefore, in an effort to improve the performance of their employees, the leadership of the company is deemed necessary to increase the emotional intelligence and commitment of their employees.